2003
DOI: 10.1089/108076803322279426
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Side-Effects Associated with Imatinib Mesylate (Gleevec®)

Abstract: This retrospective case series describes ocular side-effects associated with imatinib mesylate (Gleevec) and the clinical characteristics of these adverse reactions. A chart review of 104 patients on imatinib mesylate therapy from Oregon Health & Science University's Cancer Center were studied with regard to ocular side-effects. In addition, spontaneous reports from the Food and Drug Administration, the World Health Organization, and the National Registry of Drug-Induced Ocular Side-Effects databases were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 7 publications
1
64
2
5
Order By: Relevance
“…22,23 Conjunctival hemorrhage was noted in 14 (11%) patients in the absence of marrow suppression or systemic bleeding tendency, which is consistent with the result in a cohort of 87 GIST patients. 24 In our study, we found, for the first time, that the ocular side effects of Imatinib are independent of plasma concentration and KIT or PDGFRA mutation status, but significantly correlated with the SNPs of EGFR, SLC22A1, SLC22A5 and ABCB1, indicating that these variants might be markers for predicting the ocular toxicity in patients treated with Imatinib.…”
Section: Discussionsupporting
confidence: 84%
“…22,23 Conjunctival hemorrhage was noted in 14 (11%) patients in the absence of marrow suppression or systemic bleeding tendency, which is consistent with the result in a cohort of 87 GIST patients. 24 In our study, we found, for the first time, that the ocular side effects of Imatinib are independent of plasma concentration and KIT or PDGFRA mutation status, but significantly correlated with the SNPs of EGFR, SLC22A1, SLC22A5 and ABCB1, indicating that these variants might be markers for predicting the ocular toxicity in patients treated with Imatinib.…”
Section: Discussionsupporting
confidence: 84%
“…Ocular manifestation of edema is a recognized problem associated with imatinib use. 6 However, periorbital edema and epiphora are the two most common complications, and retinal involvement has never been reported. Since PDGF receptors are expressed in the retina, 7 it is reasonable to assume that imatinib may cause retinal edema in some patients.…”
Section: To the Editormentioning
confidence: 99%
“…From 14% of patients who had hemorrhage, 2 patients had subconjunctival hemorrhage, and in others (women) the menstruation period were became intense; after starting imatinib. Eye complication other than periorbital edema were including red eye in 5%, which in one patient was recurrent, and subconjunctival hemorrhage in two patients (3.3%), which were rarely reported in other studies even in the studies that evaluated ocular adverse effects [16] [17]. Subconjunctival hemorrhage in one patient occurred with thrombocytopenia, but the other patient did not have.…”
Section: Discussionmentioning
confidence: 86%